Cardiac Magnetic Resonance Imaging Techniques and Applications for Pericardial Diseases. (5th July 2022) - Wang, Tom Kai Ming; Ayoub, Chadi; Chetrit, Michael; Kwon, Deborah H.; Jellis, Christine L.; Cremer, Paul C.; Bolen, Michael A.; Flamm, Scott D.; Klein, Allan L.
Abstract : Cardiac magnetic resonance imaging plays a central role among multimodality imaging modalities in the assessment, diagnosis, and surveillance of pericardial diseases. Clinicians and imagers should have a foundational understanding of the utilities, advantages, and limitations of cardiac magnetic resonance imaging and how they integrate with other diagnostic tools involved in the evaluation and management of pericardial diseases. This review aims to outline the contemporary magnetic resonance imaging sequences used to evaluate the pericardium, followed by exploring the main clinical applications of magnetic resonance imaging for identifying pericardial inflammation, constriction, and effusion.